Influence of ascorbic acid and moisture levels on the physiological deterioration of cassava roots after harvest - Campos, Angela Diniz; de Carvalho, Vania Déa (Pesquisa Agropecuaria Brasileira, 1992)
It was studied the influence of ascorbic acid and moisture levels on the physiological deterioration of the cassava roots, cultivars Sonora, Guaxupé and IAC 12829 during different periods of storage. Roots from 18 months-old plants were tested and evaluations were made at 0, 2, 4, 6 and 7 days after storing under normal environment. It was observed that the highest percentage of moisture (61%) associated with the highest level of ascorbic acid (40,04 mg/100 g) in the roots of cv. Guaxupé, reduced oxidations and consequently the physiological deterioration of the roots.
Keywords: Manihot esculenta Crantz; physiological deterioration; storage; ascorbic acid